Mass-spectrometer diagnostics complex with cryogenic nitrogen trap - Tsybenko, S.A.; Kramskoj, E.D.; Korovin, V.B.; Yevsyukov, A.V.; Lozin, A.V.; Moiseenko, V.E.; Kholomyeyev, G.A.; Gribanov, V.Yu.; Kozulya, M.M.; Maznichenko, S.M.; Krasyuk, A.Yu.; Baron, D.I.; et al. (Вопросы атомной науки и техники, 2019)
The measuring complex with the cryogenic nitrogen trap [1] was created to monitor the gas composition in the stellarator Uragan-2M chamber. The complex provides several gas sampling options for the research: directly from the vacuum chamber, and condensed gas from the cryogenic trap chamber after its being heated. A new measuring cryogenic trap with its own valves was developed to implement the second method. It is necessary to provide such a state of the internal vacuum surfaces of the complex so that the background gas emission from the walls of the measuring vacuum chamber does not lead to the measurement errors in order to obtain more accurate mass spectral data. The heating of the chamber walls and continuous RF discharge at frequencies of 6…8 MHz and the power of 1 kW without a magnetic field was planned to used for this purpose. Two RF antennas, rod and planar, were designed.